Taylor Based Neuro-Genetic Algorithm For Secure And Energy Aware Multi Hop Routing Protocol In WSN - et. al., Vanitha G , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Sensor Network (WSN) is used to monitor, collect and organise the data at central location. One of the major challenges is the security and energy in WSN where energy is consumed more when the battery activates the sensors. Proposed work deals with the energy and offers an effective multihop routing in WSN called Taylor-based Neuro Genetic Algorithm (Taylor NGA) by adjusting NGA with Taylor series. This research work represents in this article, goes through two phases for multihop routing, which incorporates choosing the Cluster Head (CH) and communicating information. At first, cluster heads are taken for better data transmission; sensor nodes send information to the Cluster Head, which communicates the information to the gateway through best optimal hop . The best hop is made with the Taylor NGA to show the best performance in energy, alive nodes, delay, and throughput with estimations of 0.150, 52, 0.398, and 0.1 respectively for 100 nodes.